Comparison of negative-muscle-work energy harvesters from the human ankle: Different designs and trade-offs. (June 2021) - Liu, Mingyi; Hughes-Oliver, Cherice; Queen, Robin; Zuo, Lei
Abstract: Harvesting negative work from human walking (similar to a regenerative brake in a vehicle) has the potential to maintain the same metabolic cost as during normal walking while harvesting enough energy to power electronic devices. It is challenging to harvest power from the human ankle while only having a small influence on the human body, for which the motion of the energy harvester has to be carefully synchronized to the human body according to the human body kinematics. In order to address those challenges, we designed four different versions of ankle energy harvesters, with the same function to harvest negative muscle work in the ankle joint during walking. The performance metrics are analyzed and compared between designs. Different design parameters and their contributions to energy-harvesting performance are analyzed and discussed, and the following conclusions are provided: The spring term is the best term to minimize the influence on the human body while harvesting energy; there is a trade-off between energy harvesting performance and influence on the human body, but better designs can improve the overall performance. Design iteration in this study results in a high power design and a lightweight design, harvesting energy from the negative muscle phase of human walking with high power density over 3 W/kg and high power ratio over 50 % respectively." Highlights: Harvesting energy from negative muscle work of a human ankle. Final device weights less than 100 g, which can harvest 0.3 W of average power. The energy harvesting device synchronizes with human walking passively. By detailed modeling, the parameter choices are discussed in detail.